2001
DOI: 10.1136/jnnp.71.3.404
|View full text |Cite
|
Sign up to set email alerts
|

Combination of cyclophosphamide and interferon-beta halts progression in patients with rapidly transitional multiple sclerosis

Abstract: The eVects of combined treatment with cyclophosphamide (CTX) and interferon-(IFN-) are described in selected patients with "rapidly transitional" multiple sclerosis. This form of multiple sclerosis is extremely active with very frequent and severe attacks which produce a dramatic increase on the expanded disability status scale (EDSS). Ten patients with rapidly transitional multiple sclerosis were previously treated with interferon-, but none benefited by this treatment. Monthly treatment with intravenous CTX,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 19 publications
1
30
0
1
Order By: Relevance
“…Immunosuppressor drugs (cyclophosphamide, and AZA) combined with plasma exchange failed in secondary progressive MS [7, 8]. Experimentation with the use of immunosuppressor drugs (cyclophosphamide [9], methotrexate [10], and AZA [11]) combined with IFN-β has also produced interesting findings; recently, Markovic–Plese et al [12]have reported an open-label study demonstrating a 69% reduction in the number of contrast-enhancing lesions during the combination therapy (AZA/IFN-β 1b ) in 6 patients. Controlled studies of combined AZA and IFN-β treatment are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…Immunosuppressor drugs (cyclophosphamide, and AZA) combined with plasma exchange failed in secondary progressive MS [7, 8]. Experimentation with the use of immunosuppressor drugs (cyclophosphamide [9], methotrexate [10], and AZA [11]) combined with IFN-β has also produced interesting findings; recently, Markovic–Plese et al [12]have reported an open-label study demonstrating a 69% reduction in the number of contrast-enhancing lesions during the combination therapy (AZA/IFN-β 1b ) in 6 patients. Controlled studies of combined AZA and IFN-β treatment are not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…After the second bolus of Cyc, he significantly improved; brain MR recorded a huge reduction of edema with partial remission of the dural contrast enhancement. The laboratoristic nadir, as suggested by Cyc use in aggressive forms of Multiple Sclerosis [1], was reached thirteen days after the first Cyc dose (WBC 2.43 × 10 3 /mmc, lymphocytes 0.39 × 10 3 /u). During the treatment, the patient had fever related to Staphylococcus epidermidis infection, which was promptly treated.…”
Section: Case Presentationmentioning
confidence: 99%
“…Studies generally show that the onset of MRI effect is within 1-5 months [21]. Cyclophosphamide has also been used successfully in combination with IFN [22][23][24]. Despite different dosing schedules trials with cyclophosphamide have been consistent in showing that patients respond best if they are younger, have a shorter disease duration, and still have relapses or evidence of recent MRI activity [25,26].…”
Section: Clinical Effects and Usementioning
confidence: 99%